PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DALAM MENGOMENTARI PERSOALAN FAKTUAL - Septiani, Septani; Sunarya, Dede Tatang; Julia, Julia (Jurnal Pena Ilmiah, 2017)
This research is backgrounded by the problems that arise in the process and learning outcomes in the classroom. This research aims to improve student’s speaking ability of class VB SDN Cibeureum 1 on material commenting on factual issues by applying the model of learning picture and picture. The design of this research is refering to the design of spiral model research from Kemmis and Mc. Taggart (PTK). This study was result is conducted in three cycles, which is each cycle has increased. In the firts cycle student learning results obtained 60% percentage, in cycle II get the percentage 80%, increased in cycle III which has increased 5% become 85%. This result showed that in the application of picture and picture model can improve the abbility to speak in commenting factual issues.